Penerapan Model Beneish (1999) dan Model Altman (2000) dalam Pendeteksian Kecurangan Laporan Keuangan - Kartikasari, Rima Novi; Irianto, Gugus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Financial fraud is costly and it can be done by almost everyone within (and outside of) an organization. Prevention through early detection of fraud is an important way to reduce fraud. The objective of this research is to prove whether certain models may be utilized to detect financial statement fraud.Â This study is using Beneishâs (1999) and Altman (2000) models to detect financial statement fraud. Two selected samples that meet with pre-determined criterion have been selected and explored. The result of the study shows that those models can be used to detect financial statement fraud.